Pengawasan Hakim Melalui Pembaharuan Sistem Eksaminasi Terintegrasi di Indonesia : (Penguatan Badan Pengawasan Mahkamah Agung dan Implementasi Sistem Terintegrasi Eksaminasi Nasional (SITENAS) guna Menjaga Kualitas, Integritas, dan Kredibilitas Hakim) - Daviena Putri Anjani; Maritza Lasya Darmawan; Muhammad Atmakeno Daniswara; Mika Abdurrahman Saleh (Judex Laguens, 2024)
Judges are essentially officium nobile; the main component of the judiciary as law enforcers. In carrying out their noble duties, a judge must uphold quality, integrity and credibility in carrying out their duties. However, the reality shows a paradoxical condition where there are serious problems within the judiciary, namely the rampant abuse of authority committed by judges related to violations of the code of ethics. This is due to the weak internal supervision of judicial bodies towards judges. One of the efforts that can be made to tighten supervision of judges‘ performance is through strengthening the examination of judges’ decisions. This effort is carried out as a form of quality control over decisions because a judge's decision is a reflection of its quality. The implementation of the examination itself is not new in Indonesia because the implementation has been mandated in the Supreme Court Circular Letter (SEMA) Number 1 of 1967. However, the examination system in Indonesia has not been implemented effectively because it still experiences several obstacles in its implementation, such as weak and ageing regulations that have led to suboptimal implementation of the examination. These problems are exacerbated by the lack of clarity of the examination mechanism in Indonesia, causing uncertainty about the parameters and procedures used. For this reason, solutive measures are needed to maximise the implementation of the examination in an effort to strengthen the integrity, quality and credibility of judges through strengthening the Supreme Court Supervisory Agency accompanied by confirmation of the procedures and mechanisms of examination in Indonesia.